Theoretical and Methodological Foundations of Designing a balance Model for Reproducing Investment Potential of Institutional Sectors in the Regional System - I. V. Naumov (Финансы: теория и практика, 2019)
Reproducing investment potential of institutional sectors of the economy of any territorial system becomes a challenging issue in the light of recent trends: lack of financial resources for modernization and development of the real sector of economy, failure to successful implementing the planned strategic programs for economic development of territorial systems at macroeconomic, regional and municipal levels. A systematic approach to the formation and reproduction ofthese resources is required. In this regard, the main purpose of the work was to develop methodological foundations of designing a balance model for reproducing the investment potential of institutional sectors in the regional system. The analysis of the advantages and disadvantages of the existing approaches showed that a systematic representation of the reproduction processes of the investment potential of institutional sectors in the territorial systems requires a detailed mapping of the movement processes of financial resources between the sectors, as well as spatial features of the movement of their investment resources between the regional systems. Proposed in the work, the theoretical and methodological approach uses the basic principles of the system of national accounts: “double entry”, according to which one sector initiates the movement of financial flows, and the other accepts them; financial account structure of institutional sectors. Moran’s spatial autocorrelation and autoregression method was also applied. Thus, it provides to assess the investment resource endowment of the sectors and their sufficiency to solve the most important development problems, to determine the main uses of these resources by institutional sectors, and the riskiness of their investment activities. Such an approach provides an opportunity for state authorities and a financial regulator to assess the system of investment interconnections between institutional sectors that has developed in the regions, the problems and threats of financial development of these sectors, and to find reserves to solve them.